Predicting corporate failure of Malaysia Listed firm - Wong, Colin Tiing Ping (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Corporate failures are known to have high economic cost due to its impact on the investor, creditors, auditors, market analysts, loan officer and also to the management and employees of the affected companies. Due to this reason, over the years there are a lot of the studies on the prediction of corporate failure. Those models are including univariate analysis, risk index model, multivariate discriminant analysis and conditional probability model. In this study, the logistic regression is selected to predict the corporate failure. There are 86 unhealthy firms and another 86 healthy firms are selected in this study. The variable used in the study will different from the previous study which is only choosing the traditional financial ratio. In this study, it also evaluates the usefulness of the new selected financial ratio to predict the firm failure in Malaysia.